Second language as a compensatory resource for maintaining verbal fluency in bilingual immigrants with schizophrenia. (August 2015) - Smirnova, D.; Walters, J.; Fine, J.; Muchnik-Rozanov, Y.; Paz, M.; Lerner, V.; Belmaker, R.H.; Bersudsky, Y.
Abstract: Background and objectives. Due to the large migrations over the past three decades, large numbers of individuals with schizophrenia are learning a second language and being seen in clinics in that second language. We conducted within-subject comparisons to clarify the contribution of clinical, linguistic and bilingual features in the first and second languages of bilinguals with schizophrenia. Methods. Ten bilingual Russian(L1) and Hebrew(L2) proficient patients, who developed clinical schizophrenia after achieving proficiency in both languages, were selected from 60 candidates referred for the study; they were resident in Israel 7–32 years with 3–10 years from immigration to diagnosis. Clinical, linguistic and fluency markers were coded in transcripts of clinical interviews. Results. There was a trend toward more verbal productivity in the first language (L1) than the second language (L2). Clinical speech markers associated with thought disorder and cognitive impairment (blocking and topic shift) were similar in both languages. Among linguistic markers of schizophrenia, Incomplete syntax and Speech role reference were significantly more frequent in L2 than L1; Lexical repetition and Unclear reference demonstrated a trend in the same direction. For fluency phenomena, Discourse markers were more prevalent in L1 than L2, and Codeswitching was similar across languages, showing that the patients were attuned to the socio-pragmatics of language use. Conclusions. More frequent linguistic markers of schizophrenia in L2 show more impairment in the syntactic/semantic components of language, reflecting greater thought and cognitive dysfunction. Patients are well able to acquire a second language. Nevertheless, schizophrenia finds expression in that language. Finally, more frequent fluency markers in L1 suggests motivation to maintain fluency, evidenced in particular by codeswitched L2 lexical items, a compensatory resource. Highlights: Schizophrenia clinical markers similar in L1 and L2 validating clinical diagnosis. All linguistic markers show impairment in L2, primarily in lexical/semantic domains. Bilinguals with schizophrenia use fluency markers with unexpected social sensitivity.